Foreword: on innovations and our new appearance - Ikhsanudin Ikhsanudin (UPT Bahasa Universitas Tanjungpura, 2020)
It is important to announce that JELTIM has changed its article template. The previous template seemed a bit difficult for some authors to manage tables and figures in two-column pages. Now it is only one column and has been made easy to follow. We also changed the article’s organization, font, font size, header, footer, and authors’ affiliation section. To help ease writers who need to cite articles from this journal, we also provide “How to cite this article” section at the bottom of the first page of every article. Then, to introduce the authors more completely, we add a section of “Author’s Brief CV” at the bottom of every article’s last page. We keep the journal’s focus remains the same (innovations and materials in ELT) but the number of pages will slightly increase change into 120-130 per year. This issue (Vol. 2 No. 1) consists of five articles that form a package of innovation and materials in ELT.